Evaluation of HRM Strategies to Enhance Nurse Performance at RSU Muhammadiyah Cirebon - Vina Nurdiana Wahdah; Arih Diyaning Intiasari; Joko Mulyanto (Poltanesa, 2025)
This study aims to evaluate human resource (HR) management strategies in enhancing nurse performance at the Muhammadiyah University of Cirebon General Hospital (RSU UMC). A qualitative research approach was employed, utilizing case study and phenomenological methods through in-depth interviews, observations, documentation reviews, and questionnaires. The findings reveal that HR strategies such as selective recruitment, continuous training, and performance evaluation have been implemented and have shown a positive impact on nursing competence and service delivery. However, several challenges remain that hinder the full effectiveness of these strategies. These include high workload pressures, training content that is not entirely relevant to daily practice, performance evaluations that focus mainly on quantitative measures, and an incentive system perceived as inequitable. Furthermore, poor interprofessional communication and uneven distribution of tasks further reduce job satisfaction and motivation among nurses, ultimately affecting the quality of patient care. These limitations indicate that the current HR strategy needs to be improved and made more responsive to the real needs faced in the field. Based on the results, this study recommends the development of a more integrated HR strategy that emphasizes needs-based and adaptive training, a comprehensive and balanced performance evaluation framework, and a fair reward system that values service quality over quantity. Such improvements are essential to foster a supportive and motivating work environment, leading to increased nurse performance, higher job satisfaction, and improved patient satisfaction. This research contributes valuable insights for hospital management in designing effective HR strategies in healthcare settings.